Blood-based tri-hybrid nanofluid flow through a porous channel with the impact of thermal radiation used in drug administration - Subhalaxmi Dey; Surender Ontela; P.K. Pattnaik; S.R. Mishra (Partial Differential Equations in Applied Mathematics)
In recent trends science and technology is developed due to the utilization of modern devices of high quality and their longevity with potential efficiency. The implementation of nanoparticles now characterizes the effectiveness and efficiency. Specifically, in biomedical research drug delivery into the target, hyperthermia treatment for cancer, etc. the use of nanofluid is vital. The present article brings the characteristic of the blood-based tri-hybrid nanofluid through a porous channel embedding within a porous matrix with the interaction of magnetization and Darcy-Forchheimer inertial drag in the flow behavior. Further, the inclusion of thermal radiation, and heat source energies the heat transport properties. The formulated model for the interaction of alloy nanoparticles AA7072 and AA7075 with Zirconium oxide ZrO2 in the base liquid blood is characterized by their physical properties. The designed model is transformed into a non-dimensional form with the utilization of similarity rules. Further, a semi-analytical approach Adomian Decomposition Method (ADM) is proposed for the solution of the model. The validation with the existing article shows the convergence properties of the current methodology and the significant behavior of the factors involved in the flow phenomena are presented through graphs. Finally, the important findings are reported as; The enhanced Reynolds number decelerates the inertia force and a velocity profile shows a dual characteristic for the increasing deformation factor. Further, in comparison to the single and hybrid nanofluid, the tri-hybrid nanofluid encourages the fluid temperature due to the increasing thermal conductivity.